2004
DOI: 10.3109/13880200490893429
|View full text |Cite
|
Sign up to set email alerts
|

CNS Depressant and Analgesic Activity of a Fraction Isolated from an Ethanol Extract ofCurcuma amadaRhizomes

Abstract: In our earlier studies, an ethanol extract of Curcuma amada Roxb. rhizome was reported for anti-inflammatory activity. This ethanol extract was successively partitioned with hexane and ethyl acetate. Each fractionated extract was screened for anti-inflammatory activity, and the most active fraction was purified by column chromatography. This resulted in isolation of the active fraction F, which was characterized by spectral methods. Fraction F was studied for its effect on general behavioral studies in albino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 6 publications
(6 reference statements)
2
13
0
Order By: Relevance
“…Acetic acid induced writhing test was used for detecting peripheral analgesia, whereas hot plate and tail flick tests are most sensitive to centrally acting analgesics. 23 Studies done by Mujumdar et al, 24 Policegoudra RS et al 9 also suggest that CA has analgesic activity thus supporting our study.…”
Section: Hot Plate Methodsupporting
confidence: 84%
“…Acetic acid induced writhing test was used for detecting peripheral analgesia, whereas hot plate and tail flick tests are most sensitive to centrally acting analgesics. 23 Studies done by Mujumdar et al, 24 Policegoudra RS et al 9 also suggest that CA has analgesic activity thus supporting our study.…”
Section: Hot Plate Methodsupporting
confidence: 84%
“…The ethyl alcohol extract of mango ginger rhizome has antiinflammatory activity in acute and chronic administration in albino rats (Mujumdar et al 2000). Mujumdar et al also reported the presence of chemical compounds with hydroxyl, ester, carbonyl and olefin functional groups in ethyl alcohol extract.…”
Section: Anti-inflammatory Activitymentioning
confidence: 98%
“…This showed the bioactivity of plant. Krishnaraju et al (2006) CNS depressant and analgesic activity Observation of reduction in barbiturate sleeping time, point out CNS depressant activity Mujumdar et al (2004) Bhat et al (1981) Antipyretic activity…”
Section: Biological Activities Description Reference Brine Shrimp Letmentioning
confidence: 99%